Comparison of teachers’ and vocalists’ awareness of voice functioning, voice emission therapy and physiotherapy - Turzyński, Dominik; Sulikowski, Piotr (Journal of Education, Health and Sport, 2019)
Introduction Voice seems to us inalienable, although the lack of proper voice hygiene can result in that we may be excluded from professional activity for a long time or even completely. Therefore, it was decided to check voice functioning awareness of people who professionally speak or sing. Material and methods The research was based on a survey on a sample of 135 people from the target group. The form consisted of 28 items, including detailed questions about the type and degree of occupational exposure to voice effort, as well as the level of physical activity, occurrence of possible disorders, addiction to stimulants such as cigarettes or alcohol, and questions regarding participation in classes of correct voice emission, awareness of the existence of physiotherapeutic assistance in the field of voice rehabilitation and many others. Results The results presented and discussed in detail include the analysis of answers to questions posed in the survey, as well as the results of the Voice Handicap Index test in the group of teachers and vocalists. Conclusions Significant differences in awareness of voice functioning between teachers and vocalists were noticed. It can be stated that among teachers the deteriorating voice correlates with the increase in age. On the other hand, among vocalists, the level of perceived voice fatigue remains relatively constant while aging. Teachers who participated in the study show significantly less awareness of the principles of proper voice emission and hygiene than vocalists, as demonstrated by the Voice Handicap Index.